Serotonin, CGRP, calcitonin, CCK, somatostatin and VIP in the endocrine cells of developing rat lung - Bayrakdar, A.; Tarakci, B. Gencer (Ecole Nationale Veterinaire Toulouse, 2006)
Immunoreactivity of serotonin and some regulatory peptides (calcitonin gene related peptide (CGRP), calcitonin, cholecystokinine (CCK), somatostatin) has been demonstrated in the endocrine cells of developing lung by the peroxidase anti-peroxidase method in rat. Immunocytochemistry revealed higher density of pulmonary endocrine cells containing serotonin and CGRP in foetal and early neonatal periods than in the lungs of older rats. Serotonin positive cells were mainly located within the bronchial epithelium and in alveolar sacs, whereas the localization of CGRP positive cells was essentially restricted to alveolar sacs. The calcitonin and somatostatin-containing cells were scarcely observed whatever the developmental stages examined in bronchi, bronchioles and in alveolar sacs. The CCK expression was weak and exclusively found in alveolar sacs, and remained constant from foetus to adult stages. VIP immmunoreactivity was never detected during lung development in rat. These results suggest that serotonin and CGRP would be potent mediators involved in the lung ontogeny and in neonatal adaptation to air breathing.
Keywords: serotonin; regulatory peptides; endocrine cell; development; lung; rat